Tropical cyclone concentric eyewalls dataset during 1991-2020 - Huang, Xing; Lu, Ping; Lin, Yanluan; Huang, Xiaomeng (PANGAEA, 2022)
Concentric eyewalls (CEs) and associated eyewall replacements play key roles in tropical cyclone (TC) intensity and structure change. A long-term dataset of CEs is highly desirable for the TC research community. Based on long-term (1991-2020) global satellite observations and deep learning algorithm for image classification, we construct a global-coverage CE dataset, including 611 CE snapshots of 311 storms during 1991-2020 (30 years), documented with serial ID (SID), time, location, intensity, translation speed and direction, and distance to land. The CE dataset is based on tropical cyclone best track data (International Best Track Archive for Climate Stewardship version4, IBTrACS v4) and brightness temperature (TB) observations from multiple PMW sensors, including Special Sensor Microwave/Imager (SSM/I, F11 (1991-2000), F13 (1995-2009), F14 (1997-2008), F15 (1999-2011)), the Special Sensor Microwave Imager and Sounder (SSMIS, F17 (2007-2020)), and Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI 1997-2015).
Keywords: Concentric eyewalls; Global-coverage; Passive microwave; Tropical cyclone